MEMBANGUN LOYALITAS NASABAH DENGAN KUALITAS PELAYANAN SERTA PERAN KEPUASAN DAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Penyaluran Kredit Usaha Rakyat Di Pt. Bank Rakyat Indonesia Unit Meruya Ilir Jakarta) - Pratama, Wasis Adi; Rachbini, Didik J.; Rekarti, Endi (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research aims to examine and analyze the influence of building customer loyalty with service quality as well as role Satisfaction and Trust as Intervening variable on credit distribution KUR at BRI Unit Meruya Ilir Jakarta. he type of research is quantitative method with explanative research and analysis of this research using Structural Equation Model (SEM). The population in this research are credit borrower KUR in 2016 as many as 833 customers and sampling 200 customers with non-probability method and using accidental technique. Processing and data testing using softrelare lisrel version 8.7. The result of analysis shows that service quality has positive and significant influence on customer satisfaction, trust and loyalty, satisfaction has positive and significant influence on customer trust and loyalty, trust has positive and significant influence on customer loyalty. Suggestion in this research is bank officer need to improve their skill in serving bank customer, by giving intensive training which is done routinely so that the form of service quality given to be better. Subsequent research can replace different research models or by doing research on different types of objects, by extending research samples with different types of variables